A funcionalidade do exemplo lexicográfico em dicionário escolar para o ensino médio - Silveira Neto, Joaquim Cardoso da (2014)
This Dissertation, entitled The functionality of such lexical dictionary school to high school, analyzes the examples of UNESP Dictionary of Contemporary Portuguese, approved by the National Textbook Dictionary/2012 for distribution and use in Brazilian public schools high school, in order to reflect on the functions of the set of examples in that lexicographical work in the school context that level of Basic Education. Under the theoretical and methodological basis of lexicography, are presented and discussed the elements that make up the macro and microstructure types of dictionaries, with the aim of better understanding the overall structure of the work discussed in this research, and the criteria used by the organizing team for examples of the construction. The methodological procedures for the analysis of the object of study example guided by selection criteria sample corpus on which we applied the categories of functionality proposed by Drysdale (1987). The conclusions arrived this dissertation possible that, in regard to the roles of examples in the work effectively serve to provide context, to differentiate meanings and especially when observed as contextualizers of a given word, supplementary vocabulary definitions, the example can be used by the user as template. This research showed that monolingual dictionaries should rethink the set of examples so that the functions 4, 5 and 6 are evident, thus affecting other dimensions of the lexicon, and assisting students analyzed dictionary users. The analyzes suggest, in short, not only prospects for the development of studies and improvement of lexicographical example, but also for their functions within a lexicographical work for school use.